Assessment of captive rearing conditions on loggerhead hatchlings: Effect of handling frequency and stocking density. Issue 5 (6th May 2021) - Usategui‐Martín, Alejandro; Liria‐Loza, Ana; Valverde, Roldán A.; Pinós‐Crosas, Judit; Tuya, Fernando; Carbajal, Annaïs; López‐Bejar, Manel; Montero, Daniel
Abstract: Frequently, stranded sea turtles require rehabilitation under controlled conditions. Currently, few publications have described the conditions under which rehabilitation is to take place, particularly with respect to the hatchling life stage. To address this paucity of data, we conducted some experiments to assist rehabilitating facilities assess their handling of hatchlings. While in captivity, hatchlings are routinely handled, for example, for data collection and cleaning. Standardization of handling and housing protocols is necessary to define the most adequate rearing conditions to maintain hatchling welfare. Accordingly, the aim of this study was to assess plasma circulating corticosterone (Cort) concentration and growth, as a biomarker for the stress of hatchling loggerhead sea turtles ( Caretta caretta ) under controlled conditions. We performed two experiments to analyze handling frequency and stocking density. In both, Cort was measured and correlated with variations in animal weight and length. In handling experiments, Cort exhibited no significant increase when hatchlings were handled once a week, whereas Cort was significantly elevated when hatchlings were handled once every 2 weeks, suggesting that hatchlings have the ability to acclimate to frequent handling. However, hatchlings exhibited similar growth and mortality, regardless of handling regime. In stocking density experiments, hatchling isolation induced a significant elevation of Cort, in comparison with hatchlings placed with conspecifics at increasing densities. Growth increased in singly housed hatchlings, while mortality increased in tanks with three or more hatchlings. The results obtained suggest that Cort, growth, and mortality should be measured to assess hatchling welfare when kept under controlled conditions. Abstract : In handling experiments, Corticosterone (Cort) exhibited no significant increase when hatchlings were handled once a week (Control), whereas Cort was significantly elevated when hatchlings were handled once every 2 weeks (LHF), suggesting that hatchlings have the ability to acclimate to frequent handling. However, hatchlings exhibited similar growth and mortality, regardless of handling regime. In stocking density experiments, hatchling isolation induced a significant elevation of Cort, in comparison with hatchlings placed with conspecifics at increasing densities. Growth increased in singly housed hatchlings, while mortality increased in tanks with more hatchlings. The results obtained suggest that Cort, growth, and mortality should be measured to assess hatchling welfare when kept under controlled conditions. Research Highlights: Standardized protocols should be applied when loggerhead hatchlings are held under controlled conditions. Regular handling (once per week) is better than subjecting hatchlings to lower frequency handling protocols (every 2 weeks) as growth was not affected, and corticosterone concentration remained low. The stocking density of loggerhead hatchlings could be as high as 60 hatchlings per m 3 (three to six hatchlings per 100‐L tanks) during the first 6 months of rearing under controlled conditions, to keep appropriate fitness and low mortality rates. Isolation of individual hatchlings is not recommended, as our results suggested a significant elevation of plasma corticosterone, though growth appeared to be better and mortality was not observed.